RELATIONSHIP OF BODY IMAGE, DIET, AND NUTRITIONAL KNOWLEDGE IS BALANCED WITH THE NUTRITIONAL STATUS OF SMA YASMU MANYAR KABUPATEN GRESIK - Faridatul Kurnia Dewi Siswadi; Dwi Faqihatus Syarifah Has; Eka Srirahayu Ariestiningsih (Universitas Muhammadiyah Gresik, 2021)
The results of monitoring Nutritional Status (PSG) 2018, explained that obesity and obesity in young women aged 12-18 years decreased from 38.5% to 19.4% in overweight, and 6.7% to 4.7% in the skinny. Malnutrition and more nutritional problems in Indonesia are still common in adolescence, especially in young women. There are several factors that affect nutritional status such as body image, diet, and balanced nutritional knowledge. Tjuan from the study to analyze the relationship of body image, diet, and nutrition balanced with the nutritional status of students in Yasmu Manyar High School, Gresik Regency. This type of quantitative research uses Cross Sectional design. The number of samples as many as 45 people with sampling techniques using purposive sampling. Analyze data using Kendall-Tau. The results showed most respondents had postive body image (100%), less diet (95.5%), good nutritional knowledge (86.6%). Kendall-Tau test results between body image, diet, and nutritional knowledge balanced with nutritional status obtained a p value of 0.415 each; 0,499; 0,910. Concluded that there is no relationship between body image, diet, and nutritional knowledge balanced with the nutritional status of students at Yasmu Manyar High School in Gresik Regency. Therefore, there needs to be counseling on balanced nutrition, monitoring the nutritional status of adolescents in schools, and hopefully students to pay more attention to their intake and diet.